THE ROLE OF PREOPERATIVE BREAST MAGNETIC RESONANCE IMAGING IN PLANNING OF OPTIMUM SURGICAL TREATMENT FOR BREAST CANCER PATIENTS - O. S. Puchkova; V. E. Sinitsyn; E. A. Mershina (Вестник рентгенологии и радиологии, 2017)
Breast cancer represents a global healthcare problem. In spite of all advances in treatment regimens for breast cancer, mortality from the disease stays high in countries where population based screening has not yet been introduced. On the other hand, there is a significant decrease in mortality from breast cancer in those countries where treatment is applied in an early phase of the disease, as a result of regular, population-based screening with mammography. Although mammography is the gold standard in diagnosing breast cancer in its early stage, it has limitations in detecting breast cancer sufficiently early in the dense portion of the breast. This calls for using the multimodality approach also for screening. In addition, the high frequency of multifocal and diffuse breast cancers calls for the need to describe the true extent of the disease preoperatively. The best modality to accomplish this goal is the use of magnetic resonance imaging of the breast (MRI). This report describes the role of breast MRI in the preoperative workup of the different subtypes of breast cancer.